The holistic role of multi-level government in transformative innovation process: Theoretical framework and evidence from China - Chen, Kaihua; Xue, Zehua; Guo, Rui; Ning, Lutao (Technovation, 2025)
The lack of social impetus for transformative innovation foregrounds a more directional role for the government. However, there is limited exploration on how the government can orchestrate innovation process to promote transformative innovation. We address this gap by constructing a three-dimensional analytical framework that reflects the holistic role combinations of multi-level government across the multi-stage transformative innovation processes. Drawing on institutional theory and related research, this study conceptualizes eight critical roles of the government: planning, coordinating, allocating, investing, providing, regulating, evaluating, and publicizing in transformative innovation. By examining a recent policy experiment case of Sustainable Development Agenda Innovation Demonstration Zones in China, this study differentiates the distinct emphases of government roles across four stages of the transformative innovation process. Thus, we reveal the governance capabilities of the government throughout the innovation process to facilitate transformative innovation. Finally, we uncover the heterogeneity of preferences among central, provincial, and municipal governments and find that these multi-level governance actors have differentiated but synergistic roles given the distinct characteristics of various stages of the transformative innovation process. These governments must collaboratively utilize diverse policy instruments to maximize their roles within the scope of their administrative authority. The results suggest that policies should be holistic across the multi-stage transformative innovation processes and multi-level governments. •TI requires government support throughout the innovation process.•Governments should play eight critical roles in orchestrating TI process.•We create a matrix differentiating governments roles in stages of TI process.•Multi-level governments differ in roles and need coordinate across the TI process.•Policies need to be holistic across the TI process and multi-level governments.